E-4: THE JURISPRUDENTIAL LEGITIMACY OF INSURANCE : AND ITS LEGAL NATURE IN AFGHANISTAN - stanekzai, parwiz; mudaqiq, Abu bakr; samadi, Ahmad (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2023)
Insurance is a financial tool used for protection against financial and economic risks. The primary purpose of insurance is to compensate for financial losses and cover unexpected expenses in the event of an undesirable occurrence such as an accident, illness, or fire. The insurance system involves three parties: the insurer, the insured, and the policyholder. The insurer, or insurance company, is responsible for fulfilling the financial obligations of compensation. The insured or policyholder is the individual or organization that has committed to paying the insurance premium in exchange for coverage and purchases the insurance policy. Insurance in Afghanistan, like in other countries, is a financial tool used for protection against financial and economic risks. Various types of insurance are offered in the country, including fire insurance, home insurance, motor insurance, and commercial insurance. This study focuses on the juristic and legitimacy aspects of insurance, as some scholars consider the insurance contract to be impermissible and illegitimate. The lack of awareness and legitimacy surrounding insurance in Afghanistan has been a fundamental reason for its limited growth in the country. The study also explores the legal nature of this contract and addresses the concerns surrounding its legitimacy.